The Maqashid Sharia Construction on Inheritance in Dayak Ngaju Customs within the Tumbang Anoi Agreement - Syaikhu, Syaikhu; Hamdi, Fahmi; Ahmad, Sabarudin; Ihsan, Reza Noor; Husain, Muhammad Zidni (El-Mashlahah, 2023)
The customary inheritance settlement of Dayak Ngaju determines the distribution of heirs based on consensus referring to their compliance with the common law in the Tumbang Anoi 1894 agreement. The Dayak Ngaju Muslim community, in the settlement of inheritance disputes, still pays attention to Islamic law, but they do not ignore traditional inheritance. The research aimed to analyze the maqashid sharia construction on inheritance in Dayak Ngaju customs within the Tumbang Anoi agreement. This research was normative legal research with a historical approach. The data was in the form of primary, secondary, and tertiary legal materials. The research showed that the construction of maqashid sharia follows the mental construction, the philosophy of the distribution inheritance procedures of the Dayak Ngaju custom in the Tumbang Anoi agreement, which emphasizes the principle of peace. This agreement adopts a philosophy carried out by the diversity of its people, which highly values peace. Generally, the spirit of peace in this context also means that there is no complexity in the distribution of inheritance. The attraction of the Tumbang Anoi agreement is that people who gather in the Dayak community are one of the hundreds of Dayak community groups.